2023
DOI: 10.1039/d3cp01603j
|View full text |Cite
|
Sign up to set email alerts
|

12CO2 transition frequencies with kHz-accuracy by saturation spectroscopy in the 1.99–2.09 μm region

Abstract: Saturation spectroscopy has been used to determine absolute frequencies of 107 ro-vibrational transitions of the two strongest 12CO2 bands ofthe 2 µm region. The considered 20012-00001 and 20013-00001 bands are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, its line positions have yet to be determined with sub-MHz accuracy for transitions from the ground vibrational state. As a result, the ground state energies of 13 C 16 O 2 have not been reproduced with uncertainties at the kHz levels as those ,, of the main isotopologue 12 C 16 O 2 . Twenty-one ground combination differences, ΔE ( J ′) = R ( J ′ – 1) – P ( J ′ + 1), where J ′ is the rotational quantum number of the upper energy level, were obtained from 88 line positions in the 3001­(1,2,3)­e–00001e bands.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, its line positions have yet to be determined with sub-MHz accuracy for transitions from the ground vibrational state. As a result, the ground state energies of 13 C 16 O 2 have not been reproduced with uncertainties at the kHz levels as those ,, of the main isotopologue 12 C 16 O 2 . Twenty-one ground combination differences, ΔE ( J ′) = R ( J ′ – 1) – P ( J ′ + 1), where J ′ is the rotational quantum number of the upper energy level, were obtained from 88 line positions in the 3001­(1,2,3)­e–00001e bands.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, its line positions have yet to be determined with sub-MHz accuracy for transitions from the ground vibrational state. As a result, the ground state energies of 13 C 16 O 2 have not been reproduced with uncertainties at the kHz levels as those 15,16,39 of the main isotopologue 12 3 allows us to reproduce all experimental ground-state combination differences obtained in this work within the respective 3σ combined experimental uncertainties. By fitting 88 transition frequencies using the ground state parameters to the values determined above, we derived rovibrational spectroscopic parameters for 3001(1,2,3)e states, and they are listed in Table 3.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
“…In ref. 23, it was shown that the uncertainty on the frequency due to the optical frequency comb, the Doppler shift induced by the moving speed of the output mirror of the optical cavity and the AC/DC Stark shifts are well below the kHz level.…”
Section: Budget Errormentioning
confidence: 99%